Solve the given equation: If ${\sin ^{ - 1}}(1 - x) - 2{\sin ^{ - 1}}x = \frac{\pi }{2}$
,then the value of x is equal to
A. 0,$\frac{1}{2}$
B. 1, $\frac{1}{2}$
C. 0
D.$\frac{1}{2}$
Answer
Verified
512.7k+ views
Hint-Make use of the formula $\sin \left( {\frac{\pi }{2} + \theta } \right) = \cos
\theta $ and solve the problem
The given equation is ${\sin ^{ - 1}}(1 - x) - 2{\sin ^{ - 1}}x = \frac{\pi }{2}$,
\[{\text{On shifting 2}}{\sin ^{ - 1}}x{\text{ to the RHS we get}}\]
${\sin ^{ - 1}}(1 - x) = \frac{\pi }{2} + 2{\sin ^{ - 1}}x$
${\text{Further on shifting }}{\sin ^{ - 1}}{\text{ to the RHS, we get}}$
$\left( {1 - x} \right) = \sin \left( {\frac{\pi }{2} + 2{{\sin }^{ - 1}}x} \right)$
We know from the formula that $\sin \left( {\frac{\pi }{2} + x} \right) = \cos x$
\[So,{\text{ }}we{\text{ }}can{\text{ }}write{\text{ }}the{\text{ }}equation{\text{ }}as\;\;\;the{\text{ }}equation{\text{ }}as\;\;\;(1 - x) = \cos (2{\sin ^{ - 1}}x)\] $But{\text{ we
know the result which says 2}}{\sin ^{ - 1}}x = {\cos ^{ - 1}}(1 - 2{x^2})$
$\begin{gathered}
{\text{So, from this we get the equation to be }} \\
\Rightarrow {\text{(1 - x) = cos[}}{\cos ^{ - 1}}(1 - 2{x^2})] \\
\end{gathered} $
$We{\text{ know another formula which says cos(}}{\cos ^{ - 1}}x) = x$
$\begin{gathered}
{\text{Using this result , we can now write the equation as }} \\
\Rightarrow {\text{(1 - x) = 1 - 2}}{{\text{x}}^2} \\
\Rightarrow 2{x^2} - x = 0 \\
\Rightarrow x(2x - 1) = 0 \\
\Rightarrow x = 0{\text{ or }}x = \frac{1}{{2,}} \\
If{\text{ x = }}\frac{1}{2}, \\
LHS = {\sin ^{ - 1}}(1 - x) - 2{\sin ^{ - 1}}x = {\sin ^{ - 1}}\frac{1}{2} - 2{\sin ^{ - 1}}\frac{1}{2} =
- \frac{\pi }{6} \\
But{\text{ RHS = }}\frac{\pi }{2} \\
LHS \ne RHS \\
So,x = \frac{1}{2}{\text{ is not a solution to the given equation}} \\
\end{gathered} $
$\begin{gathered}
If{\text{ x = 0,}} \\
We{\text{ get LHS = }}{\sin ^{ - 1}}(1 - x) - 2{\sin ^{ - 1}}x = {\sin ^{ - 1}}1 - 2{\sin ^{ - 1}}0 =
\frac{\pi }{2} - 0 = \frac{\pi }{2} \\
\end{gathered} $$So,we{\text{ have LHS = RHS = }}\frac{\pi }{2}$
So, we can write x=0 is the solution for this given equation
So, option C is the correct answer
Note:Whenever we are solving these kinds of problems, we have to always choose the value
of x such that LHS=RHS. If we get any value of x such that we won't get LHS=RHS, then such
value of x should not be considered.
\theta $ and solve the problem
The given equation is ${\sin ^{ - 1}}(1 - x) - 2{\sin ^{ - 1}}x = \frac{\pi }{2}$,
\[{\text{On shifting 2}}{\sin ^{ - 1}}x{\text{ to the RHS we get}}\]
${\sin ^{ - 1}}(1 - x) = \frac{\pi }{2} + 2{\sin ^{ - 1}}x$
${\text{Further on shifting }}{\sin ^{ - 1}}{\text{ to the RHS, we get}}$
$\left( {1 - x} \right) = \sin \left( {\frac{\pi }{2} + 2{{\sin }^{ - 1}}x} \right)$
We know from the formula that $\sin \left( {\frac{\pi }{2} + x} \right) = \cos x$
\[So,{\text{ }}we{\text{ }}can{\text{ }}write{\text{ }}the{\text{ }}equation{\text{ }}as\;\;\;the{\text{ }}equation{\text{ }}as\;\;\;(1 - x) = \cos (2{\sin ^{ - 1}}x)\] $But{\text{ we
know the result which says 2}}{\sin ^{ - 1}}x = {\cos ^{ - 1}}(1 - 2{x^2})$
$\begin{gathered}
{\text{So, from this we get the equation to be }} \\
\Rightarrow {\text{(1 - x) = cos[}}{\cos ^{ - 1}}(1 - 2{x^2})] \\
\end{gathered} $
$We{\text{ know another formula which says cos(}}{\cos ^{ - 1}}x) = x$
$\begin{gathered}
{\text{Using this result , we can now write the equation as }} \\
\Rightarrow {\text{(1 - x) = 1 - 2}}{{\text{x}}^2} \\
\Rightarrow 2{x^2} - x = 0 \\
\Rightarrow x(2x - 1) = 0 \\
\Rightarrow x = 0{\text{ or }}x = \frac{1}{{2,}} \\
If{\text{ x = }}\frac{1}{2}, \\
LHS = {\sin ^{ - 1}}(1 - x) - 2{\sin ^{ - 1}}x = {\sin ^{ - 1}}\frac{1}{2} - 2{\sin ^{ - 1}}\frac{1}{2} =
- \frac{\pi }{6} \\
But{\text{ RHS = }}\frac{\pi }{2} \\
LHS \ne RHS \\
So,x = \frac{1}{2}{\text{ is not a solution to the given equation}} \\
\end{gathered} $
$\begin{gathered}
If{\text{ x = 0,}} \\
We{\text{ get LHS = }}{\sin ^{ - 1}}(1 - x) - 2{\sin ^{ - 1}}x = {\sin ^{ - 1}}1 - 2{\sin ^{ - 1}}0 =
\frac{\pi }{2} - 0 = \frac{\pi }{2} \\
\end{gathered} $$So,we{\text{ have LHS = RHS = }}\frac{\pi }{2}$
So, we can write x=0 is the solution for this given equation
So, option C is the correct answer
Note:Whenever we are solving these kinds of problems, we have to always choose the value
of x such that LHS=RHS. If we get any value of x such that we won't get LHS=RHS, then such
value of x should not be considered.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
The correct order of melting point of 14th group elements class 11 chemistry CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE